Analisis Manfaat Pendidikan Inklusi pada Anak Berkebutuhan Khusus (ABK) di Pendidikan Sekolah Dasar - Alifa, Aisha Nur; Agustin, Diah Wahyu; Mustika, Dea (TSAQOFAH, 2024)
This research aims to analyze inclusive education as an important focus in the context of educational development in Indonesia. This article explains the implementation and benefits of inclusive education in elementary schools. The research method used is qualitative using primary and secondary data. The results and discussion of this research highlight the benefits of an inclusive environment for children with special needs, the important role of school principals in communication and coordination, the benefits for special and general students, as well as the importance of collaboration between teachers and other school officials. In addition, this article emphasizes that inclusive education programs help children to be independent in daily life and improve their academic abilities, as well as providing opportunities for them to make decisions according to their talents and interests.